Remarks on the types of the New Guinea endemic Otidiphaps Gould, 1870 - Kirwan, Guy M.; Grouw, Hein van (Bulletin of the British Ornithologists' Club, 2023)
We detail the types and some other early specimens of the four taxa currently usually treated as subspecies of the New Guinea endemic, Pheasant Pigeon Otidiphaps nobilis. This material has been subject to a number of erroneous statements in the previous literature. In chronological order of description, O. n. nobilisGould, 1870, was based on a single specimen of unknown provenance and collector, now at the Natural History Museum, Tring; O. n. cervicalis E. P. Ramsay, 1880, and its objective junior synonym O. n. regalisSalvin & Godman, 1880, were based on multiple syntypes taken in 1879 (several of them the same specimens), all held in Tring (despite being previously reported as such, two specimens in Sydney appear to have no name-bearing status); O. n. insularisSalvin and Godman, 1883, is known from the two syntypes, collected in 1882 and held in Tring, and just one other specimen, taken in 1896 and held in the American Museum of Natural History, New York; and O. n. aruensisRothschild, 1928, was based on a specimen collected in June 1914, now in New York, although there is a significantly earlier specimen of this taxon in the Museum Heineanum Halberstadt.